Distancing and Bringing Near: A New Look at Mishnah Tractates ʿEduyyot and ʾAbot - Steinmetz, Devora (Hebrew Union College annual, 2002)
This paper looks at two anomalous tractates of the Mishnah, ʾAbot and ʿEduyyot, and suggests that insight may be gained into the purpose and meaning of each of these tractates by analyzing them in relation to each other. I begin by focusing on the story of Akavya ben Mehalalel in m.ʿEduyyot 5:6-7 and its connection to themes and motifs that appear at the beginning and end of the tractate. I suggest that the story encapsulates the central concerns of m.ʿEduyyot: rupture in the transmission of Torah and the attendant loss of Torah, fragmentation of the community as a result of that loss, and the challenge of shaping a cohesive community without expelling dissident members. I go on to show that these same concerns can be seen to underlie fundamental characteristics of m.ʾAbot, but that m.ʾAbot, in contrast, draws a portrait that denies the rupture, fragmentation, and exclusiveness that are in the foreground of m.ʿEduyyot. Further, I consider both the opening passage of m.ʾAbot and the concluding passage of m.ʿEduyyot as well as the teachings of Akavya in those two tractates in comparison with the early tradition in m.Ḥagigah 1:8-2:2. I argue that the ethical/religious teaching attributed to Akavya in m.ʾAbot, which I show to be central in theme to the core teachings of the miscellaneous section of m.ʾAbot, is designed to offer an alternative basis of the religious community to the bases that are seen as fragmenting, exclusive, and dangerous in m.ʿEduyyot and m.Ḥagigah.